The Effect of Work-Life Balance and Job Satisfaction on Employee Loyalty and Its Implications for Work Productivity in the Rattan Manufacturing Industry in Cirebon - Nepy Yayah Al Pasah; Anna Suzana (Majapahit Journal of Islamic Finance and Management, 2026)
This study analyzes the effect of work-life balance and job satisfaction on employee loyalty and its implications for work productivity in the labor-intensive rattan manufacturing industry in Cirebon. The topic is relevant to human resource management because production employees work under physical work demands, production targets, and workplace conditions that can shape loyalty and productivity. This study applies a quantitative explanatory approach. The population consisted of 192 employees, and the sample included 150 production employees selected using simple random sampling. The sample size provided an adequate basis for SEM-PLS analysis. Data were collected through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS. SEM-PLS was used because it can examine complex relationships among latent variables and test mediation effects in a single research model. The results show that work-life balance and job satisfaction have positive and significant effects on employee loyalty. Employee loyalty also has a positive and significant effect on work productivity. In addition, employee loyalty significantly mediates the effects of work-life balance and job satisfaction on work productivity. These findings indicate that better work-life balance and higher job satisfaction can strengthen loyalty, which then improves productivity among production employees. This study contributes to human resource management literature by integrating work-life balance, job satisfaction, employee loyalty, and productivity in one empirical model within a local labor-intensive manufacturing context. Practically, the results provide guidance for rattan manufacturing companies to develop workforce policies that support employee welfare, strengthen loyalty, and improve sustainable productivity.